Rifaximin therapy and hepatic encephalopathy: Pros and cons - Zullo, Angelo (Baishideng Publishing Group Co., Limited, 2012)
Hepatic encephalopathy (HE) is the second most common major complication in cirrhotics and it significantly impacts quality of life. Therapeutic approaches for HE treatment and prevention mainly continue to rely on ammonia-lowering strategies and non-absorbable disaccharides are currently considered the cornerstone therapy. Non-absorbable antibiotics, such as neomycin and paramomycin, are effective in treatment of acute HE episodes but their prolonged use for recurrence prevention is hampered by possible side-effects. To overcome these limitations, rifaximin use has been proposed. Rifaximin has been shown to be not superior to non-absorbable disaccharides for either HE treatment or prevention, with a similar incidence of side-effects. Cirrhosis significantly increases rifaximin absorption and this could be a cause for concern. Following long-term rifaximin therapy, Clostridium difficile colitis has been observed and Candida albicans has been isolated from 20% of patients. In addition, selection of resistant mutants of both Gram-negative and -positive bacteria in the gastrointestinal tract cannot be definitely ruled out. Electrolyte alterations (sodium and potassium) have been reported during rifaximin therapy, a warning for its long-term use in cirrhotics. Moreover, a potential interference with vitamin K production should be considered which could further impair the already altered clotting status of these patients. The therapeutic cost of rifaximin is markedly higher than non-absorbable disaccharides. While waiting for further safety data, caution should be used to limit the use of rifaximin therapy for a very short-term period in selected HE cirrhotics not responding to non-absorbable disaccharides.